Design and Evaluation of Plasmonic/Magnetic Au-MFe2O4 (M-Fe/Co/Mn) Core-Shell Nanoparticles Functionalized with Doxorubicin for Cancer Therapeutics. (2018) - Manisekaran, Ravichandran
No abstract available